EFFECT OF TWO ORGANIC NUTRIENTS AND NPK ON SOME VEGETATIV GROWTH TRAITS AND ROOT OF GRAPE TRANSPLANTS CV. SUMMER ROYAL - & Hadi, Abdulraheem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This research was conducted at the university of the University of Baghdad / Al-Jadireya during the seasons of 2016 to study the effects of applying the root stimulator Essential plus 1-0-1 and spraying of the Acadian seaweed and fertilizer (NPK) and their effects on the vegetative and root growth of grape transplants cv. Summer Royal. A factorial experiment was carried out according to the randomized complete block design with three replications .The experiment included 12 treatments, the first treatment (organic nutriment) (A0), included adding the root stimulator (Essential plus 1-0-1) to the soil with 4 ML.L-1 (A1) spraying the substance of the seaweed (Acadian) with of 1 g.L-1 (A2), and interaction (A3) and the second treatment was spraying with mineral fertilizer NPK (TOTAL GRO) with three concentrations (0,1.5,3 g.L-1) and were designated as B0,B1,B2.The organic nutrient treatment A3 significantly influenced all the measured characteristics as compared to the control treatment, as an increase of 84.38 % was achieved and 150 % for the leaf area of the transplant and the free amino acids, and root growth characteristics, as the length of the roots(39.26 %) and diameter of the roots (68.26%), as well as the surface area(26.04%) and the dry weight of the roots (48.71%).The mineral fertilization B1 and the B2 significantly impacted all the measured characteristics as compared with control , as the B2 treatment gave the maximum results in increasing the leaf area of the transplant (48.75) and the free amino acids (62.82%) and the root length (31.03%) and the roots diameter (57.05%) and the surface area of the roots (20.07%) and the dry weight of the roots (24.26%). A significant im provment was achieved in the vegetative and root growth characteristics by using organic nutriment with the mineral fertilization fcr grape transplants.